Radon exhalation rate and indoor exposure in a Brazilian coal mine - Salim, Leonardo Alfredo [UNESP]; Bonotto, Daniel Marcos [UNESP] (Springer Nature, 2019)
Radionuclides in mineral coal and related rocks are of great concern to the human health, among them the radon gas, as it has been considered the second largest cause of lung cancer by the World Health Organization (WHO). This paper describes a field and laboratorial study focusing this noble gas in the Amando Simões PI-08 coal mine, Figueira city, Paraná State, Brazil. The average 222Rn activity concentration inside the mine was ~ 227 Bq/m3, whereas the average annual effective dose received by the workers was 1.4 mSv/year, suggesting that it does not offer radon-risks to the human health.
Keywords: Coal mine; Parameters influencing the radon release; Radon exhalation rate; Radon health risk